SuperNOVA Nasal Mask Ventilation Maintains Oxygenation during Deep Sedation in High-Risk Patients: A Case Series - Rachel Kozinn; Lorraine Foley; Jessica Feinleib (Research and Practice in Anesthesiology, 2018)
With the convergence of two major medical trends, increasing obesity and the expansion of minimally invasive procedures come new challenges for airway management. In this case series we describe the use of a nasal ventilation mask, SuperNO2 VATM, in 10 patients at high-risk for sedation-induced airway obstruction and hypoxemia that required procedural sedation. This well tolerated device produced nasal oxygenation and positive airway pressure (PAP) that maintained oxygen saturation (SpO2) > 97.0% throughout the cases. These encouraging outcomes suggest the utility of pressurized nasal ventilation masks, such as the Super NO2 VATM, in patients at risk for airway obstruction requiring procedural sedation.